Long-term Outcomes of Injection Drug-related Infective Endocarditis Among People Who Inject Drugs. Issue 4 (July 2020) - Suzuki, Joji; Johnson, Jennifer A.; Montgomery, Mary W.; Hayden, Margaret C.; Price, Christin N.; Solomon, Daniel A.; Liebschutz, Jane M.; Schnipper, Jeffrey L.; Weiss, Roger D.
Abstract : Objectives: Infective endocarditis (IE) among people who inject drugs is associated with high rates of mortality and repeat episodes of endocarditis. We sought to report on longer-term clinical outcomes of patients with IE who were offered buprenorphine or methadone treatment for opioid use disorder (OUD) at their initial hospital admission. Methods: Individuals with OUD hospitalized between 2013 and 2015 with IE were included for the retrospective study. The following data were extracted from the medical record: sociodemographic data, mortality, repeat episodes of endocarditis, and evidence of ongoing buprenorphine and methadone treatment. The impact of medication use on mortality and repeat episode of endocarditis was examined using survival analysis. Results: Overall, 26 individuals were included in the study. The mean duration of follow-up was 45.0 months (SD 7.2, range 34.0–56.0). During the index admission, 8 received buprenorphine, 8 received methadone, and 10 declined medications. During the follow-up period, 4 (15.4%) individuals died and 10 (38.5%) individuals experienced a repeat episode of endocarditis. Survival analysis of mortality (log-rank P = 0.066) and repeat episode of endocarditis (log-rank P = 0.86) comparing those who received buprenorphine, received methadone, and declined medication did not differ significantly. Conclusions: Initiation of medication treatment alone may not be sufficient to impact long-term mortality and rates of repeat episode of endocarditis. More research is needed to identify optimal treatment strategies for people who inject drugs with IE.